2009
DOI: 10.1002/cncr.24326
|View full text |Cite
|
Sign up to set email alerts
|

Ductal adenocarcinoma of the prostate

Abstract: The results of this preliminary study suggested that pure ductal prostate adenocarcinoma tends to pursue an indolent clinical course and poses an increased risk for local recurrence. Local control (particularly prostatectomy) may improve the clinical outcome of patients with pure prostate ductal adenocarcinoma. These results need to be confirmed in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…3, 5 In a recently published study, Tu etal. 20 showed that, in their cohort of patients, there was a correlation between the composition of the ductal carcinoma (pure versus mixed) and the overall mortality and risk of metastasis. The mixed ductal prostate cancers appeared to be associated with an increased risk of metastasis and increased overall mortality compared with pure ductal carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…3, 5 In a recently published study, Tu etal. 20 showed that, in their cohort of patients, there was a correlation between the composition of the ductal carcinoma (pure versus mixed) and the overall mortality and risk of metastasis. The mixed ductal prostate cancers appeared to be associated with an increased risk of metastasis and increased overall mortality compared with pure ductal carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Its histologic appearance is similar to endometrial carcinoma [60]. Clinical characteristics involve presentation with a high Gleason score, local symptoms including intractable urinary symptoms, often atypical visceral metastases, and poor response to hormonal and radiotherapy [60, 61]. TMPRSS2:ERG fusion is reported at similar frequency (50%) as typical prostate acinar adenocarcinomas [62] supporting a same cell of origin.…”
Section: Other Rare Histological Variantsmentioning
confidence: 99%
“…However, Aydin et al16 stated that prostatic ductal adenocarcinoma was less malignant, slower to progress, and carried a better prognosis than the typical acinar prostate cancer. Tu et al17 reported that prognosis was comparable to other common types of prostate cancer in 25 cases of single histological type prostatic ductal adenocarcinoma, with an overall survival of 13.8 years. Some researchers believe that prognosis for prostatic ductal adenocarcinoma can be closely related to the clinical stage, tumor location, depth of invasion, and other prostate diseases 16,18,19.…”
Section: Discussionmentioning
confidence: 93%